Scientific Pedagogical Basis of Formation of Chemical Concepts for Students - Raximovich, Sharipov Shavkat; Ibroximovna, Shomuratova Dilshoda; qizi, Habibullayeva Sarvinoz Baxrom (European Journal of Life Safety and Stability (2660-9630), 2023)
This article mainly presents the theoretical basis of the methods of using innovative experiments in the teaching of chemistry.